Conceptual principles of forming tourist product quality in field of medical tourism - Baiev, Vadim; Baieva, Olena; Basyuk, Daria; Antonenko, Irina (My University, 2019)
The main factors determining the quality of the tourist product in the field of medical tourism are determined. The quality of health care provision in the field of medical tourism is a multi-component criterion, which is defined on two levels: the quality of the structure and quality of the process. The quality of the structure characterizes the conditions for the provision of medical care, and the quality of technology assesses the process of providing medical care and acts as a direct component of the quality of tourist product in the field of medical tourism.
Keywords: quality; medical tourism; quality of medical care; кафедра туристичного та готельного бізнесу